Performance investigation of bridge-less power factor correction circuit with MOSFET - Khudur, Khaleel Ali; Samad, Nabeel Mohamed Akram; Hasan, Ghanim Thiab (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The aim of this paper is to study and investigate the performance of power factor correction (PFC) circuit implemented with the semi bridge-less configuration. The transistor-diode module APT50N60JCCU2 has been used in the proposed circuit and the UCC28070 controller has been used as a controlling device for the power factor correction (PFC) circuit. Testing has been performed in two steps. In the first step, the test was conducted on (230 Vac), while in the second step, the test was conducted on (115 Vac) as alternating input voltages. The testing results of both voltages were compared and analyzed in terms of efficiency, power factor, total harmonic distortion (THD) in order to determine the efficiency of the power factor correction circuit. The results obtained indicate that this circuit has efficiency up to 97% and a power factor close to 0.91 with the input voltage of 230 V.